The application of X-ray micro Computed Tomography imaging for tracing particle movement in soil - Grayling, K.M.; Young, Scott D.; Roberts, Clive J.; de Heer, Martine I.; Shirley, I.M.; Sturrock, Craig; Mooney, Sacha J. (Elsevier, 2018)
Despite significant advances in recent years in the application of sensing and imaging technologies to the study of the hydraulic behaviour of soils, our understanding of how solutes and particulate matter move through soil is still limited and often based on idealised soil structures. The aim of this work was to use an appropriate proxy material, in this case (Decabromodiphenyl ether (DBDE)), to represent 1–2 μm sized chemical particles, frequently used in agricultural practices, in order to trace their spatial and temporal movement through a soil column. X-ray Computed Tomography (CT) was employed to map the 3D pore geometry and facilitate visualization of the concentration distribution of the highly X-ray attenuating proxy material as it was applied and subsequently leached through the soil over a 5 hour period. Simultaneously the soil eluate was collected from the bottom of each column and the concentration of proxy material measured using gas chromatography to compare with the imaged data. The method developed for visualizing the tracer material in 3D at the pore-scale was successful. The results demonstrated that the tracer material initially moved rapidly through the upper portion of the soil but subsequently became immobile, despite repeated elution with water as confirmed by imagery. Similar concentrations to those applied to the soil surface were not recorded at any point in time towards the bottom of the soil column. By visualizing the DBDE distribution in 3D it was possible to correlate the highest concentrations of the tracer material with the location of the smaller size pores (i.e. mesopores). Dynamic X-ray CT imaging of tracer materials has considerable potential as a proxy for the visualization of particulate agricultural chemicals that will assist with understanding how their transport behaviour varies both spatially and temporally.